Effects of an Intervention in Active Strategies for Text Comprehension and Recall. - Luque, Juan Luis; Gárate, Milagros; García-madruga, Juan A.; Gutiérrez, Francisco (The Spanish Journal of Psychology, 2002)
Sin resumen